2011
DOI: 10.1016/j.ijsolstr.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale damage state estimation in composites using nonlocal elastic kernel: An experimental validation

Abstract: a b s t r a c tIn recent years early detection of structural damage (detecting incubation of damage) has received great attention in the structural health monitoring field. However, extraction of lower scale information to quantify the degree of damage is a challenging task, especially when the detection is based on macroscale acoustic wave signals. All materials exhibit dependence on the intrinsic length scale. An attempt is made in this paper to extract lower scale feature from the macro-scale wave signal us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The materials dynamic softening and geometrical stiffening by applied stress, both observed for Lamb waves, represent novel effects concerning SHM. The here reported results are part of developments and respected applications based on TOF monitoring for structural health and load monitoring [3][4][5][6][7]). …”
Section: Resultsmentioning
confidence: 97%
“…The materials dynamic softening and geometrical stiffening by applied stress, both observed for Lamb waves, represent novel effects concerning SHM. The here reported results are part of developments and respected applications based on TOF monitoring for structural health and load monitoring [3][4][5][6][7]). …”
Section: Resultsmentioning
confidence: 97%
“…It is noted that PD has been used for mesoscale fracture analysis in aggregate materials, specifically in multiphase cementitious composites [102]. Shelke et al [103] addressed the multiscale estimation of damage in composite materials by means of a non-local elastic kernel. For more details on the application of PD in the context of multiscale modeling, see [104] among others.…”
Section: Multiscale Problemsmentioning
confidence: 99%
“…The changes in time of flight of the SAW due to perturbation in surface material properties were determined using cross-correlation technique. Shelke et al have shown that such small differences in TOF (>10 ns) can be obtained using cross-correlation where the sampling rate of the signal is significantly high [50]. Referring to the experimental results (Section 4), the TOF of the first arrival is determined using the cross-correlation technique applied to the time history obtained from the relationship considering piezo and non-piezo stiffening for slow transversal and longitudinal waves velocity, respectively.…”
Section: A Damage Quantification Based On Sawmentioning
confidence: 99%